Negative emotion can be “more negative” for those with high metacognitive abilities when problem-solving - Hong, Seok-sung; Bae, Jinhee; Son, Lisa K.; Kim, Kyungil (Frontiers in Psychology, 2023)
Introduction Metacognitive monitoring ability enables you to learn and solve problems more efficiently through appropriate strategies. At the same time, those who are high in monitoring ability are known to allocate more cognitive resources to the perception and control of negative emotions, as compared to those with low metacognitive ability. Therefore, while monitoring emotions may help reduce the negative emotion by enabling efficient control, it could also interrupt the use of an efficient strategy when problem-solving, as cognitive resources may be depleted. Methods To confirm this, we divided participants into groups with high and low monitoring abilities and manipulated emotions by presenting emotional videos. Subsequent to the manipulation, problem solving strategies were examined using items from the Cognitive Reflection Test (CRT). Results Results showed that those who were high in monitoring ability were shown to use more efficient problem-solving strategies than those who were lower in monitoring ability, but only in situations when positive or no emotions were manipulated. However, as hypothesized, when negative emotion was aroused, the CRT scores of high monitoring ability group were significantly lowered, decreasing to the same performance as those with low monitoring ability. We also found that metacognitive monitoring ability, when interacting with emotion, indirectly affected CRT scores, and that monitoring and control, when affected by emotion, were mediated in the process. Discussion These findings suggest a novel and complicated interaction between emotion and metacognition and warrant further research.